Accountability and Legal Liability of State-Owned Enterprise Issuers to Investors in Cases of Share Suspension Due to Default - Nugraha, Afgan; Esthi, Anggrita; Hartantien, Sinarianda Kurnia; Setiasih, Herma (International Journal on Advanced Science, Education, and Religion, 2025)
Cases of default leading to the suspension of shares of state-owned enterprise (SOE) issuers reveal structural problems in corporate governance and in the implementation of disclosure obligations in the Indonesian capital market. This study aims to analyze the accountability of SOE issuers’ corporate governance, the forms of legal liability arising from default, and the effectiveness of investor protection mechanisms when trading suspensions are imposed. Using a normative legal research method with statutory, conceptual, and case-based approaches, this study examines empirical data from the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK) from 2020 to 2024, including the cases of Garuda Indonesia, Waskita Karya, and several construction-sector issuers experiencing liquidity pressure and default risk. The findings indicate that defaults among SOE issuers are not incidental events but represent a pattern of systemic risk influenced by high leverage, moral hazard arising from implicit state guarantees, and weak supervisory functions of corporate organs. Share suspension as a market protection instrument has proven ineffective, as it is not accompanied by early risk detection mechanisms and fails to provide substantive recovery for investors. Although Articles 80 and 90 of the Capital Market Law provide a legal basis for investor claims, legal protection remains weak due to its reliance on disclosure-based regimes without guaranteed compensation. This study concludes that strengthening SOE accountability, reforming risk-based supervisory frameworks, and restructuring share suspension regulations are essential to enhance capital market integrity and ensure more effective investor protection.